Managers' pay duration and voluntary disclosures - CHENG, Qiang (Institutional Knowledge at Singapore Management University, 2021)
Given the adverse effect on their welfare, managers are reluctant to disclose bad news in a timely fashion. We examine the effect of managers' pay duration on firms' voluntary disclosures of bad news. Pay duration refers to the average period that it takes for managers' annual compensation to vest. We hypothesize and find that pay durations can incentivize managers to provide more bad news earnings forecasts. This result holds after controlling for the endogeneity of pay duration. In addition, we find that the effect of pay duration is more pronounced for firms with weaker governance and with poorer information environments, where the marginal benefits of additional disclosures are higher. We also find that these effects are stronger for firms facing lower litigation risk and for firms operating in more homogenous industries, where managers' ex-ante incentives to disclose bad news are particularly weak. Overall, we contribute to the literature by providing evidence that lengthening the vesting period of managers' compensation can induce managers to be more forthcoming with bad news.